(untitled) (Quest Journal of Management and Social Sciences, 2023)
Background: In today’s marketplace, consumers are presented with a plethora of choices when it comes to purchasing specific products. The customer preferences varying significantly compounds the abundance of options further. Objectives: The present study assesses and quantifies the intricate interplay between three pivotal elements: brand equity, customer satisfaction, and brand loyalty. Methods: The study employed an explanatory research design to establish a causal link between brand equity and brand loyalty. Due to an unknown number of shoe customers, non-probability convenient sampling was utilized. Data was collected among 403 male shoe customers residing in Kathmandu valley using a structured questionnaire through Kobo Toolbox for convenience. Analysis was performed using structural equation modelling (SEM) with the partial least square method (version 4.0). Results: The major challenges customers face when purchasing shoes are the lack of resources, competition from other shoe brands, and the unavailability of branded shoes. The SEM result shows a significant relationship between the perceived value of cost, perceived quality and life congruence with customer satisfaction, while brand identity and trust have not shown a significant relationship. Further, perceived quality, perceived value of cost, and brand identity partially mediate brand loyalty, life congruence fully mediates, and brand trust has no mediation role in brand loyalty. Lastly, respondents primarily buy shoes for special occasions and physical activities. Conclusion: The study suggests that having a high-quality brand is crucial for customers’ loyalty to the shoes. When the brand aligns with the customer’s lifestyle, it leads to satisfaction. To enhance the Nepalese shoe market, we recommend increasing brand promotion, using digital product marketing, and focusing on customer-centric activities. Paper Type: Research Paper Keywords: Brand equity, Customer satisfaction, Brand loyalty, Perceived quality, Perceived value of cost, Structural equation modelling JEL Classification: M3, L1